The solution to contemporary social crises in the light of the Prophet's ( صلی اللہ علیہ وسلم ) biography: A comparative and analytical study - Dr. Tahira Batool; Dr.Sajid Khan (Journal of Religion and Society, 2025)
The paper is an analysis of contemporary social problems and a comparison of the solutions to these problems with the biography of the Prophet Muhammad صلی اللہ علیہ وسلم . More than ever society is characterized by family breakdown, moral corruption, economic unfairness, racial inequality, terrorism and environmental destruction, and the teachings of the Prophet صلی اللہ علیہ وسلم provide a holistic and practical paradigm of social transformation on both the individual and social fronts. The study isolates some of the key social problems of this present generation and examines their causes and consequences after which the study then examines how the Prophet Shar responded excellently to similar situations he faced during his life. The research insists on the Prophet صلی اللہ علیہ وسلم treatment towards social justice, moral renewal, prosperity, balance in the family, and religious connection. As an example, they look into the degradation of the family system considering the Prophet صلی اللہ علیہ وسلم teachings about mutual respect and consultation. The zakat system and charity as a prophetic model are used to resolve economic inequality and the problem of moral corruption is overcome by bringing the notion of integrity, honesty, and focus on telling the truth of the Prophet صلی اللہ علیہ وسلم . The study also addresses how the Prophet صلی اللہ علیہ وسلم advocated gender fairness, did away with racial supremacy and prepared young people to be leaders and servants to people. Much of the study is devoted to demonstrate how the prophetic solutions can be transported both through time and space. The use of primary sources such as Quran, Hadith, and authentic Seerah literature is coupled with the modern sociological studies which allows to maintain the balance between traditional and modern approaches. The research recommends the application of prophetic principles in the education, media, economy and governance in order to achieve a just, ethical and harmonious society through practical suggestions. Finally, it can be concluded that the Seerah of the Prophet صلی اللہ علیہ وسلم is applicable as a guideline throughout time and is not only limited to Muslims, but also to the entire humankind. It gives a complete model that touches on human nature, needs in society as well as global peace. The results indicate that the implementation of these teachings in the modern environment can play a significant role in addressing the acute social issues and leading the society toward the sustainable and inclusive progress. Keywords: Seerah of the Prophet صلی اللہ علیہ وسلم , Social crises, Islamic solutions, Moral decline, Economic justice, Family system,Comparative analysis